Psihosocialni učinki uporabe storitev e-oskrbe med zaposlenimi neformalnimi oskrbovalci starejših oseb - Smole Orehek, Kaja (visokošolska dela, 2022)
The current ageing of the population means that the need for long-term care will increase significantly. The use of eCare services holds enormous potential for addressing the challenges of demographic change, yet little is known about the potential of eCare services in relation to psychosocial outcomes among employed informal carers. The aim is to identify positive and negative psychosocial outcomes of eCare services use in the post-implementation phase, explore the relationships between these outcomes, and discover how various functionalities shape psychosocial outcomes and acceptance is shaped by the identified psychosocial outcomes.A 4-month intervention study was conducted in Slovenia in 2018 and 2019 using a quasi-experimental qualitative research design. Although both quantitative and qualitative data were collected during the intervention, the qualitative methodology, where the grounded theory approach was used, played a fundamental role. A total of 44 semi-structured interviews with 22 informal carers was conducted and analysed following grounded theory coding procedures with the help of Atlas.ti 9 software.The results of the doctoral dissertation demonstrated many positive and few negative psychosocial outcomes. Older people living alone may be exposed to certain risks that can be successfully managed through use of eCare services that meet their safety needs by providing those who care for them with a reassurance of safety. Therefore, the core category identified was the reassurance of safety since it was associated with most categories and concepts, where the use of eCare services led the informal carers to have greater control over the care situation, be less worried and anxious about the potential (un)safety of the older person involved and give those who care for them peace of mind, which further impacted their acceptance. In terms of functionalities of eCare services, the motion and contact sensors and the alarm pendant elicited the most psychosocial outcomes, while it was also important that all functionalities worked properly. The identified psychosocial outcomes, their interrelationships, and the relations with acceptance are explained in a substantive conceptual model.The topic studied may be useful for developers, designers, scholars, and policymakers of eCare services to understand how end users perceive their technology through psychosocial outcomes and how they can improve it.
Keywords: ageing in place; Digitalizacija; Disertacije; Dolgotrajna oskrba; employed informal carers; functionalities of eCare services; funkcionalnosti storitev e-oskrbe; further use; grounded theory; nadaljnja uporaba; oskrba na daljavo; psihosocialni učinki; psychosocial outcomes; Socialno skrbstvo; Spletne storitve; staranje v domačem okolju; Starejši ljudje; telecare; utemeljena teorija; zaposleni neformalni oskrbovalci